2018
DOI: 10.1101/313551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory prediction errors, not performance errors, update memories in visuomotor adaptation

Abstract: Sensory prediction errors are thought to update memories in motor adaptation, but the role of 1 performance errors is largely unknown. To dissociate these errors, we manipulated visual 2 feedback during fast shooting movements under visuomotor rotation. Participants were 3 instructed to strategically correct for performance errors by shooting to a neighboring target in 4 one of four conditions: following the movement onset, the main target, the neighboring target, 5 both targets, or none of the targets disappe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In this block, no visual feedback was provided and participants were instructed to stop using any strategy they might have developed during the adaptation period. At this stage, it was impossible to determine whether this implicit process was compensating for sensory-prediction error (i.e., the difference between an action's outcome and an internal prediction of the outcome), performance error (i.e., the difference between action outcome and the task goal) or both errors (Lee et al, 2018;Mazzoni & Krakauer, 2006;Taylor & Ivry, 2011), since all of these forms of error coexisted in the full follow-through group. The fact that we saw implicit learning when the strategic explicit process was constrained (no performance error) during the task irrelevant error-clamp condition, and similar magnitude of after-effects observed in this group compared to the full follow-through group, therefore indicates that implicit learning in our experiments is driven by sensory-prediction errors.…”
Section: Follow-through Movements Allow Separation Of Opposing Memories Through Explicit and Implicit Processesmentioning
confidence: 99%
“…In this block, no visual feedback was provided and participants were instructed to stop using any strategy they might have developed during the adaptation period. At this stage, it was impossible to determine whether this implicit process was compensating for sensory-prediction error (i.e., the difference between an action's outcome and an internal prediction of the outcome), performance error (i.e., the difference between action outcome and the task goal) or both errors (Lee et al, 2018;Mazzoni & Krakauer, 2006;Taylor & Ivry, 2011), since all of these forms of error coexisted in the full follow-through group. The fact that we saw implicit learning when the strategic explicit process was constrained (no performance error) during the task irrelevant error-clamp condition, and similar magnitude of after-effects observed in this group compared to the full follow-through group, therefore indicates that implicit learning in our experiments is driven by sensory-prediction errors.…”
Section: Follow-through Movements Allow Separation Of Opposing Memories Through Explicit and Implicit Processesmentioning
confidence: 99%
“…When adapting to novel environments, motor memories that capture the relationships between the desired behavioral consequences and the motor commands are formed as internal models in the central nervous system (CNS) (Kawato, 1999;Shadmehr & Mussa-Ivaldi, 1994;Shadmehr et al, 2010;. The internal models are consecutively updated based on errors in preceding trials (Franklin et al, 2008;Herzfeld et al, 2014;Lee et al, 2018;Mattar & Ostry, 2007;Oh & Schweighofer, 2019;Scheidt et al, 2001;Takahashi et al, 2001). Smith et al (2006) proposed a computational model that comprises a fast-learning, fast-forgetting memory process and a slow-learning, slow-forgetting memory process; see also (Coltman et al, 2019;Huberdeau et al, 2015;McDougle et al, 2015;Sing & Smith, 2010;Turnham et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kurtzer and colleagues instructed a group of participants to "match the effort" of their baseline movements when confronted with a force field and found that it diminished learning compared to a group instructed to "match the kinematics" (Kurtzer et al 2003). This disengagement by instruction seems incompatible with implicit adaptation in visual perturbation experiments, which proceeds so stereotypically that it can sometimes harm task performance Taylor and Ivry 2011;Schween et al 2014;Lee et al 2018a). Keisler and Shadmehr, assuming a two-process model with a "fast" and a "slow" component of force field learning , found that a declarative memory task retroactively interfered with the fast component (Keisler and Shadmehr 2010), suggesting that this fast component, being susceptible to declarative memory load, might be explicit in nature (Morehead et al 2011).…”
Section: Introductionmentioning
confidence: 99%